People with autoimmune hepatitis and celiac disease have a milder liver disease course and a better chance of immunosuppressive treatment withdrawal. (March 2023) - Pezzato, F.; D'Ovidio, E.; Perini, L.; Bonaiuto, E.; Rollo, P.; Catanzaro, E.; Peviani, M.; Russo, F.P.; D'Odorico, A.; Zingone, F.; Floreani, A.; Cazzagon, N.
Abstract : Background: In people with Autoimmune Hepatitis (AIH), the diagnosis of Celiac Disease(CD) is 3-times more frequent than in general population. In paediatric patients with AIH and CD a milder course of AIH and higher chances of immunosuppressive therapy withdrawal were reported. Aim: To assess frequency of CD in AIH, and to analyse the features and the long-term response to immunosuppressive treatment in patients with AIH associated with CD(AIH-CD) compared to patients without CD(AIH-non-CD). Methods: A retrospective cohort study including all consecutive people with an established diagnosis of AIH in adulthood was performed. Exclusion criteria were the presence of overlap syndromes or concomitant liver diseases. Decompensation-free survival was calculated according to Kaplan-Meier estimates; data were censored at the date of last visit or the occurrence of cirrhosis decompensation. Results: 166 consecutive people(80% female, median age 52) with diagnosis of AIH between 1990 and 2021 and followed-up for a median of 63(24-125) months at the Gastroenterology Unit of the University Hospital of Padova were included. Eighteen percent had cirrhosis at diagnosis. Nine people (5.4%) had a histologically confirmed diagnosis of CD. People with AIH-CD were treated with significantly lower doses of prednisone at 2 years from diagnosis (2.5 vs. 5 mg/day, p= 0.007) and at 3 years from diagnosis were more likely to have stopped steroids (83% vs. 31%, p=0.007) compared to AIH-non-CD. On long-term observation, immunosuppressive therapy withdrawal was more frequent in AIH-CD compared to AIH-non-CD (44% vs. 13%, p=0.01) and the need for immunosuppressive reintroduction was similar (p=n.s.). On the other hand, we did not found differences regarding cirrhosis development, cirrhosis decompensation, liver-related deaths or number of relapses between people with AIH-CD and AIH-non-CD. Conclusions: In our cohort, CD is present in 5.4% of people with AIH. In people with AIH-CD we observed a milder course and immunosuppressive therapy has been effectively withdrawn more frequently compared to AIH-non-CD.